The Impact of the Applied Marketing Strategies on Subscription Rate in Multichoice Uganda - Trevor Ian Muhuma (Uganda Christian University, 2024)
This dissertation investigates the demographic characteristics, satisfaction levels, and recommendations of Multichoice Uganda subscribers within the Ugandan entertainment industry. The study is guided by three objectives: To examine the demographic characteristics of Multichoice Uganda subscribers. To assess customer satisfaction levels with Multichoice Uganda's services and their correlation with subscription renewals and word-of-mouth referrals. To propose actionable recommendations for Multichoice Uganda and other stakeholders in the Ugandan entertainment industry based on customer insights and preferences. Using probability sampling, the research methodology involved conducting a comprehensive survey of Multichoice Uganda subscribers. This approach ensured that each subscriber had an equal chance of being selected, enhancing the representativeness of the sample population. The survey collected data on demographic variables such as gender, age, and occupation, allowing for a detailed analysis of subscriber characteristics. Additionally, satisfaction levels with various aspects of Multichoice services, including content quality, customer service, value for money, technical support, and advertisements, were assessed. The findings revealed a diverse demographic profile among Multichoice Uganda subscribers, with a slight gender imbalance and a focus on younger to middle-aged demographics. Satisfaction levels varied across different aspects of Multichoice services, with content quality generally rated positively but customer service and value for money receiving mixed reviews. Subscribers expressed a moderate likelihood of subscription renewal and advocacy, with notable opportunities for improvement in customer engagement and service delivery. Based on these findings, actionable recommendations were proposed for Multichoice Uganda and other stakeholders in the Ugandan entertainment industry to optimize marketing strategies, enhance customer satisfaction, and drive sustainable growth. Overall, this dissertation contributes to a deeper understanding of customer dynamics within the Ugandan entertainment industry, offering insights that can inform strategic decision-making and drive positive outcomes for Multichoice Uganda and the broader ecosystem of stakeholders.